Флешмоб у роботі сучасної бібліотеки у контексті соціальної комунікації - Якименко, Н. О.; Комлик, Ю. О. (Видавництво Львівської політехніки, 2014)
The article was analyzed practice and theoretical aspects of using flash mob and the Internet-recourse in connection of library with readers. Also were characterized advantages and defects of this collaboration.
Keywords: library; reader; torrent of information; flash mob; internet-resource; librarian flash mob